2017
DOI: 10.1186/s13062-017-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2A is a component of the ZEB1/2 network that regulates TGFB1-induced epithelial to mesenchymal transition

Abstract: BackgroundThe transition between epithelial and mesenchymal phenotypes (EMT) occurs in a variety of contexts. It is critical for mammalian development and it is also involved in tumor initiation and progression. Master transcription factor (TF) regulators of this process are conserved between mouse and human.MethodsFrom a computational analysis of a variety of high-throughput sequencing data sets we initially inferred that TFAP2A is connected to the core EMT network in both species. We then analysed publicly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…TFAP2A has been implicated in cancer proliferation, invasion, and epithelial-to-mesenchymal transition (EMT) [ 33 , 34 ]. However, it remains unclear whether TFAP2A is involved in tumor-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFAP2A has been implicated in cancer proliferation, invasion, and epithelial-to-mesenchymal transition (EMT) [ 33 , 34 ]. However, it remains unclear whether TFAP2A is involved in tumor-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that TFAP2A promotes EMT procession by regulating TGF-β signaling in cancer cells [ 33 ] and TFAP2A regulates tumor growth via hypoxia inducible factor-1a (HIF-1a) signaling in nasopharyngeal carcinoma and NSCLC [ 34 , 41 ], whereas the HIF-1a pathway has been confirmed to promote angiogenesis [ 42 ]. To validate the role of TFAP2A in anlotinib resistance, we performed TFAP2A knockdown in AR cells and found that tumor-induced angiogenesis was decreased in AR cells by TFAP2A knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of TFGB3 in embryogenesis can be related to its role in the epithelial-mesenchymal transitions (EMT), which enables cell movement and morphogenesis (Zavadil and Böttinger, 2005). During gastrulation, EMT is observed in the generation of the primitive mesoderm, the cell migration into the primitive node and the establishment of the three embryonic layers (Blomberg et al, 2008;Dimitrova et al, 2017). CITED1 (or MSG1), which encodes for the transcriptional factor Cbp/p300-interacting transactivator 1, has been described to be involved during embryogenesis (Dunwoodie et al, 1998;Gerstner and Landry, 2007) and placentation (Rodriguez et al, 2004;Sparrow et al, 2009) in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although a vast majority of the studies conducted so far have portrayed AP-2α as a regulator of lineage specification during embryogenesis and cancer development and progression in adults (Eckert et al, 2005;Kolat et al, 2019), there is indication that AP-2α may play a key role in cellular fibrogenic response. AP-2α can promote epithelial-mesenchymal transition (EMT), a process critical to tissue fibrosis, by up-regulating TGF-β expression (Zhang et al, 2017) and by forming a complex with ZEB1/2, the E-box binding transcriptional regulators of EMT (Dimitrova et al, 2017). Ross et al (2019) have recently reported that deletion of TFAP2A (the gene encoding AP-2α) significantly attenuates the TGF-β induced maturation of myofibroblasts although the underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%